Contemporary review of the organ care system in lung transplantation: potential advantages of a portable ex-vivo lung perfusion system. (1st November 2016) - Schmack, Bastian; Weymann, Alexander; Mohite, Prashant; Garcia Saez, Diana; Zych, Bartlomiej; Sabashnikov, Anton; Zeriouh, Mohamed; Schamroth, Joel; Koch, Achim; Soresi, Simona; Ananiadou, Olga; De Robertis, Fabio; et al.
ABSTRACT: Introduction: Lung transplantation remains the definite treatment for various end-stage lung diseases. Cold flush perfusion, the standard method for organ procurement has severe limitations. Organ Care System (OCS; TransMedics, Inc., Andover, USA) is an approved method to preserve hearts for transplantation that allows for greatly reduced cold ischemic time. Consequently, the use of an adapted OCS lung as a portable full ex-vivo lung perfusion system in lung transplantation is currently under close evaluation. Areas covered: The aim of this article is to review the advantages and the role of the OCS in the field of lung transplantation by reviewing the latest literature and evaluating this novel procurement technique in the context of conventional methods like cold flush and regular ex-vivo lung perfusion. Expert commentary: The use of OCS in the field of lung transplantation has great potential for improved patients outcomes and is justified in cases with (i) marginal donor lungs, (ii) foreseeable long time of transportation (iii) high-risk recipient or donor /recipient profiles, particularly in the setting of an overall increasing need for suitable donor organs. Results from two major multi-centre prospective studies are pending to objectively assess the possible advantages of this portable ex-vivo lung perfusion system.